Contemporary Romanian Migrations to Serbia: Stages, Actors, Reasons - Sorescu-Marinkovic, Annemarie (Balcanica Posnaniensia. Acta et studia, 2017)
This paper aims at offering insight into the contemporary migration of Romanians towards Serbia, starting with the interwar period, continuing with the communist rule and focusing on the period after the fall of the Romanian communist regime, in 1989. What this study does is delimit the stages of the Romanian migration to Serbia, identify the social categories taking part in these migratory processes, the preferred regions for settling in Serbia, as well as the reasons behind people’s decision to leave the country. I also show how the Romanian emigrants relate to the Romanian autochthonous communities in Serbia (the Vlachs of Eastern Serbia and the Romanians of Vojvodina), in which they usually settle. After presenting the theoretical background relating to ethnic migrations, I introduce a new theoretical concept, reverse ethnic migration, which best fits the situation of contemporary Romanian migrants to Serbia. These migrations take place from a majority (Romanians in Romania) towards a national minority (Romanians or Vlachs in Serbia), thus in an „opposite” direction. The migrations are not state supported and they are individual in most of the cases. I argue that the interwar migrations were state planned, being the result of the Yugoslav-Romanian School Convention from 1933; those taking place during communism were triggered, in many instances, by political reasons; while the post-communist migration was labour oriented.